Mushroom‐shaped structures formed in Acinetobacter baumannii biofilms grown in a roller bioreactor are associated with quorum sensing–dependent Csu‐pilus assembly. (30th March 2022) - Romero, Manuel; Mayer, Celia; Heeb, Stephan; Wattanavaekin, Krittanont; Cámara, Miguel; Otero, Ana; Williams, Paul
Summary: There is currently a need to develop simple biofilm models that facilitate investigation of the architecture/biology of mature bacterial biofilms in a consistent/standardized manner given their environmental and clinical importance and the need for new anti‐biofilm interventions. This study introduces a novel biofilm culture system termed the rolling biofilm bioreactor (RBB). This easily operated system allows adherent microbial cells to be repeatedly exposed to air/solid/liquid interfaces optimizing biofilm growth. The RBB was exploited to investigate biofilm formation in Acinetobacter baumannii . High levels of A . baumannii biofilm biomass reproducibly accumulate in the RBB and, importantly, undergo a maturation step to form large mushroom‐shaped structures that had not been observed in other models. Based on image analysis of biofilm development and genetic manipulation, we show how N ‐acylhomoserine lactone‐dependent quorum sensing (QS) impacts on biofilm differentiation, composition and antibiotic tolerance. Our results indicate that extracellular DNA (eDNA) is a key matrix component in mature Acinetobacter biofilms as the mushroom‐like structures consist of dense cellular masses encased in an eDNA mesh. Moreover, this study reveals the contribution of QS to A . baumannii biofilm differentiation through Csu pilus assembly regulation. Understanding the mechanisms of structural development of mature biofilms helps to identify new biofilm eradication and removal strategies.